Olfactory bulb — as the source of accumulation and differentiation of neural stem cells in postnatal human brain - Semenova, V. M.; Medvedev, V. V. (Ukrainian Neurosurgical Journal)
The authors of the review summarize the results of the last decade research concerning the processes of neurogenesis in adult central nervous system. The main attention is paid to the neurophysiology and morphology of olfactory bulb as a source of accumulation of neural stem cells (NSC) which migrate into this formation from subventricular zone of lateral ventricles and differentiate there into mature neurons and glial cells. The authors have analysed evidence of the activation of neurogenesis in postnatal animals’ brain during certain pathological conditions (forebrain ischemia, seizures). They examined perspectives of NSC’s utilization in the treatment of neurodegenerative and posttraumatic diseases of central nervous system.